Implementation of Multicultural Values Through Religious Program at Integrated Islamic Junior High Schools in Palembang City - Julius Saputra; Kasinyo Harto; Saipul Annur (STAI Hubbulwathan Duri, 2024)
This study examines how multicultural values are implemented in the curriculum and activities at SMP IT in Palembang City, identifying the supporting and inhibiting factors. This type of research is qualitative with a descriptive approach. Data collection uses interview techniques, participant observation, documentation studies. Data analysis uses the process of data collection, data reduction, data presentation and verification or drawing conclusions. This research found that implementing multicultural values at SMP IT in Palembang City by implementing religious moderation as early as possible can be implemented in the school environment such as the values of tawassuth, tawazun, i'tidal, tasamuh, musawah, and shura. The implementation of multicultural values through religious activity programs at SMP IT in Palembang City needs to be evaluated with the aim of finding out to what extent the religious activity program can be according to plan and if necessary, revisions or innovations will be made so that the goals achieved are more effective.